2014
DOI: 10.1155/2014/601571
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Gastroesophageal Reflux Disease in Type II Diabetes Mellitus

Abstract: Background/Aims. Patients with type II diabetes mellitus (DM) were known to have higher prevalence of gastroesophageal reflux disease (GERD) in the Western countries, but data on the impact of GERD on DM patients in our country are scarce. The aim of this study was to evaluate the prevalence of GERD in type II DM patients in Shanghai, China, and to explore its possible risk factors. Methods. 775 type II DM cases were randomly collected. Reflux Disease Questionnaire (RDQ) was used to check the presence of GERD.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
0
8
1
1
Order By: Relevance
“…Published literature suggests that as many as 75% of patients visiting diabetic clinics report significant GI symptoms. 29 Type II diabetes mellitus has been described as a possible risk factor for the development of GERD. In this survey, approximately 20% of the cases were associated with diabetes mellitus, in line with earlier studies in Asian population indicating a prevalence of approximately 18-25%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Published literature suggests that as many as 75% of patients visiting diabetic clinics report significant GI symptoms. 29 Type II diabetes mellitus has been described as a possible risk factor for the development of GERD. In this survey, approximately 20% of the cases were associated with diabetes mellitus, in line with earlier studies in Asian population indicating a prevalence of approximately 18-25%.…”
Section: Discussionmentioning
confidence: 99%
“…In this survey, approximately 20% of the cases were associated with diabetes mellitus, in line with earlier studies in Asian population indicating a prevalence of approximately 18-25%. 29 Arthritic patients usually receive anti-inflammatory agents like COX inhibitors or corticosteroids and hence are more prone for PUD and GERD. Similarly, patients with cardiovascular disorders are usually on aspirin therapy, predisposing them to APD.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Several studies in other countries have reported more GERD prevalence in patients with DM than in the general population. 9,10 In this study, we aimed to estimate the prevalence of symptomatic GERD in diabetic patients and to investigate GERD's potential associations with diabetic microvascular and macrovascular complications, and with patients' sociodemographic and clinical characteristics.…”
mentioning
confidence: 99%
“…Second, RDQ scores < 12 were set as one of the diagnostic criteria for silent GERD for the first time, since patients with minor symptoms who do not qualify for the diagnosis of GERD may have the same clinical results as the patients without any symptoms. Furthermore, a score of 12 is universally accepted as a diagnostic criterion for GERD in studies with Chinese subjects [ 3 , 24 , 37 , 38 ]. However, there are also several potential limitations of this study.…”
Section: Discussionmentioning
confidence: 99%